Barriers To Change: A Case Study Investigation On Factors Hindering Organizational Transformation - Perdhana, Mirwan Surya; Permanasari, Yarra Waninda (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2019)
Regardless the size, organizations need to transform themselves to meet the demand of current competition era. Nevertheless, many organizations were failed to implement change despite having a clear organizational strategy. The aim of this research is to investigate factors hindering organizational transformation and change. To achieve such aim, a qualitative case-study investigation was conducted in a State-owned Enterprise located in Greater Semarang, Central Java, Indonesia, involving 10 participants which consists of top manager, middle managers, line managers and the workers.The findings of this study reveals that transformation effort in the company were hindered due to several factors: commitment and initiatives issues, change management issues, language issues, communication issues, and time constraint issues. Implication for theory and managerial practice were also discussed.